FBXO22 degrades nuclear PTEN to promote tumorigenesis - Meng-Kai Ge (Nature Portfolio, 2020)
Loss of nuclear PTEN is associated with aggressive cancers. Here the authors show that nuclear PTEN is more susceptible to ubiquitin-mediated proteasomal degradation than cytoplasmic PTEN, and identify FBXO22 ubiquitinates and degrades nuclear PTEN to promote tumorigenesis.